1980
DOI: 10.1111/j.1460-2695.1980.tb01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Macrocrack Growth in Tempered Hy80, Hy130, and 4140 Steels:threshold and Mid-?K Range

Abstract: The rate of propagation of macrofatigue cracks down to near threshold was measured in air in three tempered martensitic steels; HY80, HY130 and 4140 (650°C temper). The value of A&,, was determined by the load-shedding technique in center notched panel specimens. Of the three steels, 4140 tempered at 65WC had the lowest AK,,, 3 3 MN/m3IZ, while HY80 had the highest, 4.2 MN/rn3". The 4140 (650°C temper) is intermediate in strength between HY80 and HY130. The results are discussed in terms of a recent theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The steels QIN and HYI30 were examined by Jones [9] in dry air, laboratory air and seat water. The steels HY80 and HYI30 (HY80 is almost identical to QIN) were examined by Kwun and Fine (24] in laboratory air and dry argon. These investigations showed that the two steels have similar crack growth rates in dry air or dry argon.…”
Section: Austenitic Stainless Steel Aluminium and Titanium Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The steels QIN and HYI30 were examined by Jones [9] in dry air, laboratory air and seat water. The steels HY80 and HYI30 (HY80 is almost identical to QIN) were examined by Kwun and Fine (24] in laboratory air and dry argon. These investigations showed that the two steels have similar crack growth rates in dry air or dry argon.…”
Section: Austenitic Stainless Steel Aluminium and Titanium Alloysmentioning
confidence: 99%
“…The steels Q1N and HY130 were examined by Jones [9] in dry air, laboratory air and sea water. The steels HY80 and HY130 (HY80 is almost identical to Q1N) were examined by Kwun and Fine [24] in laboratory air and dry argon. These investigations showed that the two steels have similar crack growth rates in dry air or dry argon, but t i ( K n a x /oyI2 = 0," tIKmax the growth rate increases much more for HY130 when the environment is changed to laboratory air than it does for Q l N (the same trend does not apply for the seawater environment).…”
Section: Examination Of Figs 3 and 5 Suggested That Yield Strength Anmentioning
confidence: 99%
“…The magnitude of inelastic strains can be judged from the data given in Fig. 5 which shows typical static and cyclic stress-strain curves for steels of various strengths [22]; the dash-and-dotted line represents the maximum value of inelastic strain per cycle, which was determined earlier [23] during the investigation of fatigue and inelasticity of various metals and alloys under high-cycle loading ( Table 1). The inelastic strain has even lower values at the stresses equal to fatigue limits of metals and alloys on a base of 10 7 cycles.…”
mentioning
confidence: 99%